The effect of tax revenue, investment and foreign debt on poverty level - Sessu, Andi (Advances in Social Sciences Research Journal, 2019)
Indonesia economic development, especially in the three macro-economic variables, namely tax revenues, foreign debt and developments of investment from 2002 to 2017 can be categorized as increasing and the number of poor people can also be categorized as decreasing. The results of multiple regression analysis show that tax receipts and investment developments have not been able to reduce poverty levels, because with high tax revenues originating from high individual and corporate taxes can affect the level of prices by itself demand decreases, as a result companies also reduce production and investment activities affect the decline in employment opportunities that can give birth to unemployment and poverty, one of which is also the reason for the receipt of taxes in part by corruption by certain people and the entry of high foreign workers. The foreign debt can reduce the poverty level, because the greater the foreign debt the more developing development activities that can absorb labor that affect the decline in unemployment and poverty rates. Multiple correlation coefficient (r) of 0.947 means that there is a very strong relationship between all three variables studied, while the coefficient of determination (R2)= 0.896 or 89,6% of the number of poor can be affected by variables of tax revenue, loans overseas and investment development. The remaining 10.4% is influenced by other factors. The results of this study explain the importance of government policies to always suppress foreign labor and imports as well as increase the quality of human resources both character quality and human resource competencies. Preservation of natural resources is very important to be done through sustainable efforts, both those carried out by the community, companies and the government so that the national economy will increase in the future.